Socialismo e liberalismo: considerações sobre a social-democracia - Pereira, Pedro Peña Barbosa (2019)
This research aims to discuss distances and proximities between socialism and liberalism. For this purpose, we carried out a qualitative research starting from a historical narrative about socialism and liberalism highlighting social contexts that have driven the respective thoughts to find themselves within the Estate. We begin by recapitulating the events of the French Revolution, where we follow the ideological structure of the thoughts in order to emphasize their constitution by their opposites. In this way, we map the trajectory of the emergence of social democracy in socialist thought. Afterwards, we enter the liberal field, where we show its structuring as an ideology and how these structures have opened up a heterogeneity within thought. This strategy allowed us to map two antagonistic trunks of thought that we translated into the tension between social reformers (new liberals) and the laissez-faire’s supporters (first liberalism/classical liberalism), an attrition that culminated in neoliberalism. Thus, we identify ordoliberalism and show its proximity to social democracy and the news liberals